Leadership Skills Development in the Digital Era: A Systematic Analysis ofTraining and Learning Approaches - Muhammad Syafiq (Public Studies and Business Administration Journal (PUSBA), 2024)
Leadership skills development in the digital era is crucial for navigating the complexitiesof today's rapidly evolving business landscape. This systematic literature reviewexplores various training and learning approaches aimed at enhancing leadershipcompetencies within the context of digital transformation. By synthesizing existingscholarly literature, the review identifies key trends, challenges, and opportunities inleadership development in the digital age. It examines the conceptualization ofleadership in the digital era, theoretical foundations of leadership development, andmodels of digital leadership competencies. Furthermore, the review explores a widerange of training and learning approaches, including traditional methods and innovativedigital technologies such as e-learning platforms, virtual reality simulations,gamification, and social learning networks. The findings of this review offer insights intoeffective strategies for developing digital-era leaders and highlight implications forpractice, research, and policy.